2015
DOI: 10.4254/wjh.v7.i8.1097
|View full text |Cite
|
Sign up to set email alerts
|

Role of antiviral therapy in the natural history of hepatitis B virus-related chronic liver disease

Abstract: interactions among HBV, hepatocytes, and the host immune system. Natural history studies of chronic hepatitis B (CHB) infection have shown an association between active viral replication and adverse clinical outcomes such as cirrhosis and hepatocellular carcinoma. The goal of therapy for CHB is to improve quality of life and survival by preventing progression of the disease to cirrhosis, decompensation, end-stage liver disease, hepatocellular carcinoma (HCC) and death. This goal can be achieved if HBV replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…In China, HBV infection is moderately endemic, and chronic hepatitis B (CHB) is the main cause of cirrhosis, liver de-compensation, and hepatocellular carcinoma (HCC) 2 . Among chronic HBV infection patients, those with significant liver inflammation have a much greater risk of cirrhosis, liver de-compensation, and HCC 3 . According to the guidelines for chronic HBV infection, it is critical to identify patients with significant liver inflammation, and treat them immediately 4 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In China, HBV infection is moderately endemic, and chronic hepatitis B (CHB) is the main cause of cirrhosis, liver de-compensation, and hepatocellular carcinoma (HCC) 2 . Among chronic HBV infection patients, those with significant liver inflammation have a much greater risk of cirrhosis, liver de-compensation, and HCC 3 . According to the guidelines for chronic HBV infection, it is critical to identify patients with significant liver inflammation, and treat them immediately 4 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis B viral (HBV) infection, a risk factor for chronic liver diseases including cirrhosis, hepatocellular carcinoma, and liver failure, remains a global health problem . Studies have indicated that effective antiviral therapy may reduce development of liver‐related complications, which is of great significance for the long‐term clinical prognosis for patients . Therefore, accurate and timely staging of liver fibrosis, especially significant fibrosis and cirrhosis, is important for the timing of antiviral therapy in chronic hepatitis B (CHB) patients in effort to maximize the benefit of antiviral therapy.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, encouraging SVR12 statistics in patients with decompensated cirrhosis receiving Harvoni ® and ribavirin suggest that these patients will respond to the most recent wave of anti‐HCV medications . The fate of patients with advanced liver disease who achieve SVR is uncertain, but the liver transplant community remains optimistic that the efficacy of HCV antiviral therapy will parallel the successes seen with hepatitis B over the last 10–15 yr, in which antiviral treatment has appreciably decreased the need for LT for decompensated liver disease, with HCC being the primary complication for the majority of patients on treatment . Nevertheless, the treatment of HCV in cirrhotic patients should be carefully monitored at experienced LT centers, after thorough consideration of the risks and benefits.…”
Section: Discussionmentioning
confidence: 99%